2009
DOI: 10.1242/dev.037556
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofDlk1, PtpruandKlhl1as novel Nurr1 target genes in meso-diencephalic dopamine neurons

Abstract: The orphan nuclear receptor Nurr1 is essential for the development of meso-diencephalic dopamine (mdDA) neurons and is required, together with the homeobox transcription factor Pitx3, for the expression of genes involved in dopamine metabolism. In order to elucidate the molecular mechanisms that underlie the neuronal deficits in Nurr1 -/-mice, we performed combined gene expression microarrays and ChIP-on-chip analysis and thereby identified Dlk1, Ptpru and Klhl1 as novel Nurr1 target genes in vivo. In line wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 52 publications
7
96
0
10
Order By: Relevance
“…This analysis identified 19 genes that are regulated by both Pitx3 and En1, six of which were previously identified as Nurr1 target genes (Jacobs et al, 2009b;Jacobs et al, 2011) (Fig. 3C).…”
Section: Research Articlementioning
confidence: 85%
“…This analysis identified 19 genes that are regulated by both Pitx3 and En1, six of which were previously identified as Nurr1 target genes (Jacobs et al, 2009b;Jacobs et al, 2011) (Fig. 3C).…”
Section: Research Articlementioning
confidence: 85%
“…−/− mice (Jacobs et al, 2009a). Conditional knockout of Foxa1/2 during development drastically reduces Nurr1 expression (Ferri et al, 2007), probably by a direct expression control, but possibly owing to general developmental defects in the knockout mice.…”
Section: Development Analysis Of Nurr1mentioning
confidence: 99%
“…The reciprocal relationship between Pitx3/RA and the expression of Dlk1 potentially reflects an important role for endogenous RA signaling in DA neurons of the SNc. Next to the effect of RA treatment on Th, Dlk1 and D2R expression, we verified the extent to which RA treatment affected the expression of other Nurr1 and Pitx3-dependent genes (Jacobs et al, 2009a;Jacobs et al, 2009b) involved in mdDA function. We found that expression of Vmat2 (Slc18a2 -Mouse Genome Informatics), Dat (Slc6a3 -Mouse Genome Informatics) and Ahd2, all downregulated in the absence of Pitx3, cannot be rescued by embryonic supplementation of RA.…”
Section: Introductionmentioning
confidence: 98%
“…In this study, we aimed to pinpoint the molecular effects of RA on gene transcription in Pitx3-deficient mdDA neurons and provide evidence for a relationship between Pitx3/RA and the expression of Dlk1, Th and D2R (Drd2). Interestingly, Dlk1 was recently identified as a novel Nurr1 target gene (Jacobs et al, 2009b). The reciprocal relationship between Pitx3/RA and the expression of Dlk1 potentially reflects an important role for endogenous RA signaling in DA neurons of the SNc.…”
Section: Introductionmentioning
confidence: 99%